Identification of synthetic precursors of amphetamine-like drugs using Raman spectroscopy and ab initio calculations: beta-Methyl-beta-nitrostyrene derivatives - Milhazes, Nuno (2004)
The present work reports a vibrational spectroscopic study of several beta-methyl-beta-nitrostyrene derivatives, which are important intermediates in the synthesis of illicit amphetamine-like drugs, such as 3,4-methylenedioxymethamphetamine (MDMA), 3,4-methylenedioxyamphetamine (MDA), p-methoxyamphetamine (PMA) and 4-methylthioamphetamine (4-MTA). A complete conformational analysis of 3,4-methylenedioxy-beta-methyl-beta-nitrostyrene (3,4-MD-MeNS), 4-methoxy-beta-methyl-beta-nitrostyrene (4-MeO-MeNS), 4-methylthio-beta-methyl-beta-nitrostyrene (4-MeS-MeNS), was carried out by Raman spectroscopy coupled to ab initio MO calculations--both complete geometry optimisation and harmonic frequency calculation. The Raman spectra show characteristic features of these precursors, which allow their ready differentiation and identification. It was verified that the conformational behaviour of these systems is mainly determined by the stabilising effect of pi-electron delocalisation.